Presentations, demos, and training sessions - Wallwork, Adrian (Guides to Professional English, 2014)
This is the first book ever for non-native speakers on how to conduct technical demos and training sessions. You will also learn how to present your company, and explain your products and services. The book is designed to help both those who have never done presentations before, as well as those whose English is already good but who want to improve their presentation skills. The focus is on language, rather than on the creation of slides from a technical/artistic point of view. This book will help you to: prepare and practice a well organized, interesting and memorable presentation give effective demos and training sessions either on site or via audio/video conference highlight the essential points you want the audience to remember avoid problems in English by using short easy-to-say sentences involve your audience, check their understanding, and deal with their questions improve your pronunciation overcome problems with nerves and embarrassment motivate your audience to listen and act on what you have said There is an introduction for trainers on how to teach presentations and demos within a Business English course. Adrian Wallwork is the author of over 30 books aimed at helping non-native English speakers to communicate more effectively in English. He has published 13 books with Springer Science+Business Media.  Other books in this Professional English series: Email and Commercial Correspondence CVs, Resumes, and LinkedIn User Guides, Manuals, and Technical Writing Meetings, Negotiations, and Socializing Telephone and Helpdesk Skills